2015
DOI: 10.1097/md.0000000000002274
|View full text |Cite
|
Sign up to set email alerts
|

The Seroprevalence of Toxoplasma gondii in Chinese Population With Cancer

Abstract: Toxoplasmosis is fatal in the immunocompromised individuals such as cancer patients with chemotherapy. Clinical toxoplasmosis in cancer patients is a great public health concern in China. We performed this meta-analysis to assess the seroprevalence and odds ratios (ORs) of Toxoplasma gondii in Chinese population with cancer compared with those without.A methodical literature search was conducted with the help of the PubMed, Web of Knowledge, Embase, Chinese Web of Knowledge, Wanfang, and Chongqing VIP database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…2,23,32 The prevalence is lower in USA, Mexico and China, being 10.8%, 20.26% and 6.31%, respectively, mostly due to the good hygienic measures, successful educational programs to alert people, precise diagnostic tests for women of childbearing age and pregnant women, industrialization of animal husbandry as well as well-established monitoring systems and improved rules in meat inspection. 11,34,35 In Ethiopia, toxoplasmosis prevalence rate of 75% has been observed which may be corroborated by the abundance of infected cats and food animals, low levels of hygiene and living in sub-standard conditions. 28 Pregnant women are substantial targets of T. gondii infection and the seroprevalence of infection among this population in Iran Table 1 Baseline characteristics of included studies.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…2,23,32 The prevalence is lower in USA, Mexico and China, being 10.8%, 20.26% and 6.31%, respectively, mostly due to the good hygienic measures, successful educational programs to alert people, precise diagnostic tests for women of childbearing age and pregnant women, industrialization of animal husbandry as well as well-established monitoring systems and improved rules in meat inspection. 11,34,35 In Ethiopia, toxoplasmosis prevalence rate of 75% has been observed which may be corroborated by the abundance of infected cats and food animals, low levels of hygiene and living in sub-standard conditions. 28 Pregnant women are substantial targets of T. gondii infection and the seroprevalence of infection among this population in Iran Table 1 Baseline characteristics of included studies.…”
Section: Discussionmentioning
confidence: 98%
“…Being one of the marvelous parasites, T. gondii still possesses a relatively high rate of prevalence in different mankind societies as well as various animal species. 1,3,8,11,21,[28][29][30][31][32] The objective of this systematic review and meta-analysis was to estimate the prevalence of T. gondii infection in human and animal populations in Iran premised on records obtained from literature review. We searched 7 databases among which 7 papers were included with 105,139 examined samples obtained from different hosts and weighted overall prevalence was 37% (95% CI = 31-43) ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…studies showed a seroprevalence of 20.59% for the cancer population, compared to 6.31% for the population without cancer [17]. Other groups of researchers reported that people with ocular neoplasia had higher rates of toxoplasmosis [18].…”
Section: Discussionmentioning
confidence: 99%